1982
DOI: 10.1159/000233133
|View full text |Cite
|
Sign up to set email alerts
|

<i>Nippostrongylus brasiliensis </i>Infection in the Rat: Effects of Surgical Removal of Peyer’s Patches, Mesenteric Lymph Nodes and Spleen

Abstract: The influence of the surgical removal of Peyer’s patches, mesenteric lymph nodes and spleen has been examined on the host response to Nippostrongylus brasiliensis infection in the rat. In animals subjected to these procedures, no effects were observed on whole blood or plasma histamine levels, peripheral blood leucocytosis or reaginic antibody levels, intestinal mast cell numbers or histamine content, nor on faecal egg output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…This result indicates that GALT and/or NF‐κB is not necessary for normal expulsion of adult N. brasiliensis from the small intestine, because the mutant aly/aly mice lacks NF‐κB [7] and show the systemic absence of secondary lymphoid tissues [8]. These results supported the previous report that surgical removal of all visible PP and MLN had no effects on immune responses against N. brasiliensis [6]. However, the present study also showed that aly/aly mice developed more severe H. polygyrus infections than control mice as demonstrated by increased faecal egg counts with reduced immune responses.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This result indicates that GALT and/or NF‐κB is not necessary for normal expulsion of adult N. brasiliensis from the small intestine, because the mutant aly/aly mice lacks NF‐κB [7] and show the systemic absence of secondary lymphoid tissues [8]. These results supported the previous report that surgical removal of all visible PP and MLN had no effects on immune responses against N. brasiliensis [6]. However, the present study also showed that aly/aly mice developed more severe H. polygyrus infections than control mice as demonstrated by increased faecal egg counts with reduced immune responses.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, GALT has been considered to be a major source of Th2 cells during N. brasiliensis infection. However, it has been reported that surgical removal of all visible PP and MLN has no effect on peripheral blood leucocytosis, intestinal mast cell number or egg output [6]. The authors of that study discussed the possibility that the mice infected with N. brasiliensis can activate Th2 responses in a GALT‐independent manner.…”
Section: Introductionmentioning
confidence: 99%
“…In 1963, Archer first suggested that the rabbit appendix might represent the bursa homolog (Archer et al, 1963), an idea that was supported by others . Several groups have shown that X irradiation and removal of the appendix, Peyer's patches, and sacculus rotundus in rabbits leads to a selective defect in antibody production (Cooper et al, 1966;Perey et al, 1970;Heatley et al, 1982). On the other hand, the lymphoid aggregates, associated with the epithelium, such as the tonsil and Peyer's patches, do not appear to have a true lymphoepithelium in which primary B-cell development occurs (Perey, 1971).…”
Section: Mammalian Bursa Equivalentmentioning
confidence: 99%
“…However, a recent study concluded that mesenteric lymphadenectomy did not affect the levels of parasite-specific IgE [7], We have also used this method to examine the source of serum IgE and of specific anti-parasite IgE anti bodies in Nb-infested rats and to extend previous observations [8] on the presence of specific homo cytotropic antibody-secreting cells in the thoracic duct lymph.…”
Section: Introductionmentioning
confidence: 95%